Evaluation of Microbe-Driven Soil Organic Matter Quantity and Quality by Thermodynamic Theory - Jianwei Zhang (American Society for Microbiology, 2021)
Microbial communities are known to be important drivers of organic matter (OM) accumulation in terrestrial ecosystems. However, despite the importance of these soil microbes and processes, the mechanisms behind these microbial-SOM associations remain poorly understood.